Patient-Centered Tablet Application for Improving Medication Adherence after a Drug-Eluting Stent - Shah, Vicki; Dileep, Anandu; Dickens, Carolyn; Groo, Vicki; Welland, Betty; Field, Jerry; Baumann, Matthew; Flores, Jose D.; Shroff, Adhir; Zhao, Zhongsheng; Yao, Yingwei; Wilkie, Diana J.; et al. (Frontiers in Public Health, 2016)
Background/aims This study’s objective was to evaluate a patient-centered educational electronic tablet application, “My Interventional Drug-Eluting Stent Educational App” (MyIDEA) to see if there was an increase in patient knowledge about dual antiplatelet therapy (DAPT) and medication possession ratio (MPR) compared to treatment as usual. Methods In a pilot project, 24 elderly (≥50 years old) research participants were recruited after a drug-eluting stent. Eleven were randomized to the control arm and 13 to the interventional arm. All the participants completed psychological and knowledge questionnaires. Adherence was assessed through MPR, which was calculated at 3 months for all participants who were scheduled for second and third follow-up visits. Results Relative to control, the interventional group had a 10% average increase in MPR. As compared to the interventional group, more patients in the control group had poor adherence (<80% MPR). The psychological data revealed a single imbalance in anxiety between the control and interventional groups. On average, interventional participants spent 21 min using MyIDEA. Discussion Consumer health informatics has enabled us to engage patients with their health data using novel methods. Consumer health technology needs to focus more on patient knowledge and engagement to improve long-term health. MyIDEA takes a unique approach in targeting DAPT from the onset. Conclusion MyIDEA leverages patient-centered information with clinical care and the electronic health record highlighting the patients’ role as a team member in their own health care. The patients think critically about adverse events and how to solve issues before leaving the hospital.